Animal-eRNAdb: a comprehensive animal enhancer RNA database. Issue Volume 50:Issue D1(2022) (22nd September 2021) - Jin, Weiwei; Jiang, Guanghui; Yang, Yanbo; Yang, Jianye; Yang, Wenqian; Wang, Dongyang; Niu, Xiaohui; Zhong, Rong; Zhang, Zhao; Gong, Jing
Abstract: Enhancer RNAs (eRNAs) are a class of non-coding RNAs transcribed from enhancers. As the markers of active enhancers, eRNAs play important roles in gene regulation and are associated with various complex traits and characteristics. With increasing attention to eRNAs, numerous eRNAs have been identified in different human tissues. However, the expression landscape, regulatory network and potential functions of eRNAs in animals have not been fully elucidated. Here, we systematically characterized 185 177 eRNAs from 5085 samples across 10 species by mapping the RNA sequencing data to the regions of known enhancers. To explore their potential functions based on evolutionary conservation, we investigated the sequence similarity of eRNAs among multiple species. In addition, we identified the possible associations between eRNAs and transcription factors (TFs) or nearby genes to decipher their possible regulators and target genes, as well as characterized trait-related eRNAs to explore their potential functions in biological processes. Based on these findings, we further developed Animal-eRNAdb (http://gong_lab.hzau.edu.cn/Animal-eRNAdb/ ), a user-friendly database for data searching, browsing and downloading. With the comprehensive characterization of eRNAs in various tissues of different species, Animal-eRNAdb may greatly facilitate the exploration of functions and mechanisms of eRNAs.